2022
DOI: 10.3390/jcm11082261
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Safety of Expanded Hemodialysis Compared with Hemodialysis Using High-Flux Dialyzer during a Three-Year Cohort

Abstract: Expanded hemodialysis (HD) equipped with a medium cut-off (MCO) membrane provides superior removal of larger middle molecules. However, there is still little research on the long-term benefits of expanded HD. Over a three-year period, this observational study evaluated the efficacy and safety profile of expanded HD for inflammatory cytokines, including IL-6. We conducted a prospective cohort study to investigate the inflammatory cytokine changes and a retrospective observational cohort study to investigate lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…These findings hamper the inflammatory suppressive role of individualized dialysate cooling. Other studies involving hemodialysis [ 34 ] and peritoneal dialysis [ 35 ] patients found a tendency for IL-6 levels to remain stable over 3 and 1 years of follow-up, respectively. The shorter duration of follow-up in the present study, as well as the distinct dialysis modalities of extended hemodialysis and peritoneal dialysis, may account for these contradictory findings.…”
Section: Discussionmentioning
confidence: 98%
“…These findings hamper the inflammatory suppressive role of individualized dialysate cooling. Other studies involving hemodialysis [ 34 ] and peritoneal dialysis [ 35 ] patients found a tendency for IL-6 levels to remain stable over 3 and 1 years of follow-up, respectively. The shorter duration of follow-up in the present study, as well as the distinct dialysis modalities of extended hemodialysis and peritoneal dialysis, may account for these contradictory findings.…”
Section: Discussionmentioning
confidence: 98%
“…16 A 3-year follow-up observational study involving 42 patients, reported no difference in darbepoetin alfa use between MCO and high-flux dialysis. 17 The potential benefits of improved removal of MUTs on ESA dose and ERI have been observed with online hemodiafiltration. 18 In a small, 6-month randomized controlled study that compared Theranova 500 with hemodiafiltration (which is considered superior to high-flux hemodialysis in removing MUTs), the Theranova group showed evidence of better MUT clearance and a statistically non-significant downward trend in weekly ESA dosing and lower ERI, while hemoglobin levels remained stable.…”
Section: Discussionmentioning
confidence: 99%
“…4). This allows augmented clearances of molecules in a very broad spectrum [38,40], without significant losses of albumin [41]. Several studies suggest an improved erythropoietin responsiveness [42,43], improved muscle strength, improved nutritional status in parallel to a reduction of chronic inflammation [44].…”
Section: Hemodialysismentioning
confidence: 99%